Impact on CD4+ CD25High-CD127low regulatory T (Treg) cells of neoadjuvant therapy for rectal cancer patients - Liu Maoxi; Liu Haiyi (Indian Journal of Pathology and Microbiology)
Background: The efficacy of neoadjuvant therapy for rectal cancer has not been assessed. Objective: To evaluate proportional changes in peripheral blood immune cells in rectal cancer patients after neoadjuvant therapy and assess the relationship between tumor regression and regulatory T (Treg) cells. Materials and Methods: Rectal cancer patients who had received neoadjuvant therapy prior to surgery at Shanxi Cancer Hospital between January and September 2018 were enrolled in the study. Treg, CD4+ T, CD8+ T, NK, B cells, and CD4+/CD8+ ratio in peripheral blood before and after neoadjuvant therapy were measured by flow cytometry. Patients were divided into down-staging and control groups, depending on their responses to neoadjuvant therapy. Results: A total of 108 patients were enrolled. The proportion of Treg cells was significantly lower after neoadjuvant therapy (P < 0.05) but no changes were seen in CD4+ T, CD8+ T, NK, B cells, or CD4+/CD8+ ratio (all P > 0.05). There were 76 patients in the down-staging and 32 in the control groups. There were no significant differences in clinical parameters between down-staging and control groups (all P > 0.05). There were no significant differences in immune cell proportions between the two groups prior to neoadjuvant therapy (all P > 0.05). Treg, CD4+ T, and B cells were all significantly lower in the down-staging group after neoadjuvant therapy than before (P < 0.05). CD4+/CD8+ ratios were lower (P < 0.05) while proportions of Treg and natural killer (NK) cells did not change after neoadjuvant therapy in the control group. Following neoadjuvant therapy, Treg and B cells were lower while CD4+ and CD4+/CD8+ ratios were higher in the down-staging group compared to the control group (P < 0.01). Conclusion: Treg cells may constitute a reference for judging the effect of neoadjuvant therapy in rectal cancer patients.